Preventable risk factors for osteoporosis in postmenopausal women: Systematic review and meta-analysis - Jyoti Thulkar; Shalini Singh; Shashi Sharma; Tanmay Thulkar (Wolters Kluwer Medknow Publications, 2016)
Background and Objective: The osteoporosis is becoming public health problem in India and neighboring Asian countries. As the environmental risk factors for osteoporosis in women are similar in these countries, the study was planned to compare risk factors for osteoporosis in postmenopausal women in Asian countries. Materials and Methods: A systematic literature search was done in August 2015. The period included for this search was from January 2005 to December 2014. The search was done for India and neighboring countries. The final analysis was done on the studies from India, China, Korea, and Japan. The literature search was done in PubMed and Google Scholar using key words, "Osteoporosis" and "Menopause" and "Risk factor." Results: The pooled prevalence for the osteoporosis in postmenopausal women is 41%, but in India alone, it is 53%. Various risk factors are studied in China as compared to other countries. Adequate calcium intake and various exercises were found to be useful modifiable factors. Other factors like age, height, and postmenopausal status cannot be modified. Conclusion: Adequate calcium and Vitamin D intake and combinations of various exercises can be considered as preventive measures for osteoporosis in postmenopausal women.